The human milk microbiome is minimally associated with breastfeeding practices - Ruomei Xu; Mark P. Nicol; Ali S. Cheema; Jacki L. McEachran; Ashleigh H. Warden; Sharon L. Perrella; Zoya Gridneva; Donna T. Geddes; Lisa F. Stinson (Scientific Reports)
Abstract The human milk microbiome is dominated by typical oral and skin bacteria, suggesting that bacterial communities from the infant mouth and maternal skin contribute to the development of the human milk microbiome. It is postulated that breastfeeding characteristics, such as breastfeeding frequency and duration, could lead to different levels of exposure to oral and skin bacteria, and subsequently, altered bacterial profiles in human milk. To investigate the associations between breastfeeding characteristics and the human milk microbiome, this study analysed milk samples collected from 56 participants at 3 months postpartum by full-length 16 S rRNA gene sequencing. Breastfeeding characteristics (breastfeeding frequency, total 24 h breastfeeding duration, and 24 h milk removal volume) were recorded by the participants using the 24 h test weighing protocol. The milk microbiome was largely robust to breastfeeding practices, with only one association detected between breastfeeding characteristics and the milk microbiome. Duration of breastfeeding from the sampled breast (per 24 h) was weakly positively associated with the relative abundance of Streptococcus salivarius (P = 0.035). No associations with alpha nor beta diversity were detected. In conclusion, variations in breastfeeding characteristics do not have a major impact on the composition or diversity of the human milk microbiome.